2023
DOI: 10.1186/s12903-023-02810-9
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric sleep-disordered breathing in Shanghai: characteristics, independent risk factors and its association with malocclusion

Abstract: Objectives This study aimed to determine the prevalence and independent risk factors of SDB, and explore its association with malocclusion among 6–11-year-old children in Shanghai, China. Methods A cluster sampling procedure was adopted in this cross-sectional study. Pediatric Sleep Questionnaire (PSQ) was applied to evaluate the presence of SDB. Questionnaires including PSQ, medical history, family history, and daily habits/environment were comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The research group performed a cross-sectional study of a total of 715 children, and found tonsil hypertrophy plays an essential role in the direction of dentofacial development 18 . Additionally, a total of 3433 subjects were studied and found the prevalence of OSA in primary students in the Chinese urban population was highly associated with mandibular retrognathia 19 .…”
Section: Orthodontic Appliance Accompanied With Orofacial Myofunction...mentioning
confidence: 99%
“…The research group performed a cross-sectional study of a total of 715 children, and found tonsil hypertrophy plays an essential role in the direction of dentofacial development 18 . Additionally, a total of 3433 subjects were studied and found the prevalence of OSA in primary students in the Chinese urban population was highly associated with mandibular retrognathia 19 .…”
Section: Orthodontic Appliance Accompanied With Orofacial Myofunction...mentioning
confidence: 99%
“…The consequences of untreated SDB can extend beyond immediate sleep disturbances and may lead to various comorbidities, including growth abnormalities, cardiovascular issues, immune disorders, and metabolic disturbances [ 5 ]. Moreover, SDB can be associated with orofacial and dentofacial characteristics, potentially linked to malocclusion and other craniofacial abnormalities, leading to further complications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%